Działalność pozalekcyjna polskich szkół na Zaolziu w upowszechnianiu kultury i polskości - z badań nad prasą zaolziańską = After classes activities of Polish schools in Zaolzie disseminating of culture and Polishness - from research on Zaolzie press - Micherda, Magdalena (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
There are currently 25 primary schools in Zaolzie with Polish as the language of instruction and the only Polish Junior High School (the equivalent of a Polish high school) in Cesky Tesin. The specificity of Polish education in Zaolzie lies, among others, in the close cooperation of Polish schools in Zaolzie with local institutions and organizations in the field of promoting culture among student. Polish culture is particularly close to the inhabitants of Zaolzie.
Keywords: Zaolzie; szkoły polskie; działalność pozalekcyjna; kultura; polskość; Polish schools; after classes activities; culture; Polishness